Branched-chain ketoacids derived from cancer cells modulate macrophage polarization and metabolic reprogramming - Cai, Zhengnan; Li, Wan; Brenner, Martin; Bahiraii, Sheyda; Heiss, Elke H.; Weckwerth, Wolfram (Frontiers in Immunology, 2022)
Macrophages are prominent immune cells in the tumor microenvironment that can be educated into pro-tumoral phenotype by tumor cells to favor tumor growth and metastasis. The mechanisms that mediate a mutualistic relationship between tumor cells and macrophages remain poorly characterized. Here, we have shown in vitro that different human and murine cancer cell lines release branched-chain α-ketoacids (BCKAs) into the extracellular milieu, which influence macrophage polarization in an monocarboxylate transporter 1 (MCT1)-dependent manner. We found that α-ketoisocaproate (KIC) and α-keto-β-methylvalerate (KMV) induced a pro-tumoral macrophage state, whereas α-ketoisovalerate (KIV) exerted a pro-inflammatory effect on macrophages. This process was further investigated by a combined metabolomics/proteomics platform. KMV and KIC altered macrophage tricarboxylic acid (TCA) cycle intermediates and increased polyamine metabolism. Proteomic and pathway analyses revealed that the three BCKAs, especially KMV, exhibited divergent effects on the inflammatory signal pathways, phagocytosis, apoptosis and redox balance. These ﬁndings uncover cancer-derived BCKAs as novel determinants for macrophage polarization with potential to be selectively exploited for optimizing antitumor immune responses.